Biocompatible Micron‐Scale Silk Fibers Fabricated by Microfluidic Wet Spinning. Issue 20 (31st July 2021) - Lüken, Arne; Geiger, Matthias; Steinbeck, Lea; Joel, Anna‐Christin; Lampert, Angelika; Linkhorst, John; Wessling, Matthias
Abstract: For successful material deployment in tissue engineering, the material itself, its mechanical properties, and the microscopic geometry of the product are of particular interest. While silk is a widely applied protein‐based tissue engineering material with strong mechanical properties, the size and shape of artificially spun silk fibers are limited by existing processes. This study adjusts a microfluidic spinneret to manufacture micron‐sized wet‐spun fibers with three different materials enabling diverse geometries for tissue engineering applications. The spinneret is direct laser written (DLW) inside a microfluidic polydimethylsiloxane (PDMS) chip using two‐photon lithography, applying a novel surface treatment that enables a tight print‐channel sealing. Alginate, polyacrylonitrile, and silk fibers with diameters down to 1 µm are spun, while the spinneret geometry controls the shape of the silk fiber, and the spinning process tailors the mechanical property. Cell‐cultivation experiments affirm bio‐compatibility and showcase an interplay between the cell‐sized fibers and cells. The presented spinning process pushes the boundaries of fiber fabrication toward smaller diameters and more complex shapes with increased surface‐to‐volume ratio and will substantially contribute to future tailored tissue engineering materials for healthcare applications. Abstract : A 3D‐printed microfluidic wet‐spinning platform is developed to fabricate silk fibers with diameters down to 1 µm as tissue for cell culture. The fibers shape is tailored by the nozzle‐geometry and the mechanical fiber properties are controlled by the spinning process parameters.